2023
DOI: 10.1128/jvi.01694-22
|View full text |Cite
|
Sign up to set email alerts
|

Trimeric, APC-Targeted Subunit Vaccines Protect Mice against Seasonal and Pandemic Influenza

Abstract: Subunit vaccines present only selected viral proteins to the immune system and allow for safe and easy production. Here, we have developed a novel vaccine where influenza hemagglutinin is presented in the natural trimeric form and then steered toward antigen-presenting cells for increased immunogenicity. We demonstrate efficient induction of antibodies and T-cell responses, and demonstrate that the vaccine format can protect mice against influenza subtypes H1N1, H5N1, and H7N1.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 53 publications
0
3
0
Order By: Relevance
“… 42 Even though, MERS-CoV monomeric RBD or spike protein were able to generate desirable protecting immune responses, other studies with other viruses have shown that trimeric native like oligomeric envelope proteins may induce long lasting immune responses. 43 , 44 Recently, Chang Chi-Chieh et.al have expressed the MERS-CoV-S1 ectodomain trimeric protein in the recombinant baculovirus expression system and showed in the presence of QS-21 adjuvant, that the S1 trimeric proteins were able to elicit a strong and enduring memory T cell response. 45 …”
Section: Discussionmentioning
confidence: 99%
“… 42 Even though, MERS-CoV monomeric RBD or spike protein were able to generate desirable protecting immune responses, other studies with other viruses have shown that trimeric native like oligomeric envelope proteins may induce long lasting immune responses. 43 , 44 Recently, Chang Chi-Chieh et.al have expressed the MERS-CoV-S1 ectodomain trimeric protein in the recombinant baculovirus expression system and showed in the presence of QS-21 adjuvant, that the S1 trimeric proteins were able to elicit a strong and enduring memory T cell response. 45 …”
Section: Discussionmentioning
confidence: 99%
“…There is still room for improvement and advancement. Differences in cell lines and culture circumstances, particularly in the transition from serum-containing medium to serum-free medium, may have a major impact on the cell properties [23,24].…”
Section: Discussionmentioning
confidence: 99%
“…Antigen-presenting cells (APCs), especially DCs, play a critical role in the interaction between innate immunity and adaptive immunity after infection or immunization. Targeting antigens toward molecules or chemokine receptors on APCs, such as CD11c [ 23 ], DEC-205 [ 24 ], Xcr1 [ 25 ], major histocompatibility complex class II (MHC-II) [ 26 ] and macrophage galactose-type lectin (MGL) [ 27 ], could dramatically stimulate enhanced immunogenicity. To date, monoclonal antibodies [ 28 ], single chain variable fragments (scFvs) [ 23 ], nanobodies [ 29 ] and DC-targeting peptides (DCpep) [ 30 ] have been employed in the design of DC-targeting vaccines.…”
Section: Introductionmentioning
confidence: 99%